Macroprudential policy, house price fluctuation and household consumption - Qi, Yang; Qin, Haixiao; Liu, Peide; Liu, Jianxu; Raslanas, Saulius; Banaitienė, Nerija (Technological and Economic Development of Economy, 2022)
House purchasing has become an important asset allocation choice for most families in China. House price fluctuation is also one of the important factors that leads to systematic risks in the financial market, which might cause economic crises and then reduce consumption. Since China formally established the dual-pillar management framework of macroprudential policy in 2019, it has played a crucial role in maintaining the stability of house prices. This article employs the mediating effect model to comb the internal mechanism of the interaction between macroprudential policies, housing prices, and household consumption and test by the panel data of 30 provinces and cities in China from 2004 to 2019. Experience implies that macroprudential policy can not only stabilize consumption demand directly and effectively, but also affect consumption indirectly through the cross of the real estate market and the credit market. Further research has also found that macroprudential policies may fail between regions with higher GDP and high-income groups. This finding will contribute to research on the relationship between macroprudential policies and real economics. In addition, it would be helpful in making policies to increase consumption.